A balnearização da baixada de Araruama e a emergência da “Costa do Sol”, Rio de Janeiro (1940-1960) - Leticia Parente-Ribeiro; Marcos Paulo Ferreira de Góis; Marcelo Antônio Sotratti (Confins)
In the 1940s and 1950s, the urbanization of the Araruama lowlands on the eastern coast of the state of Rio de Janeiro occurred under the auspices of a broad program of economic recovery in the state of Rio de Janeiro. Directed by the state government, actions for the region included major works of sanitation, the expansion and reconfiguration of the road system and the elaboration of urbanization plans. The aim was to attract tourist flows and to guide urban occupation through residential use during summer vacations and weekends. The transformations of the coastal zones, with their rhythms and uncertainties, contributed to the consolidation of “balnearization” as the main factor of integration of the Araruama lowlands to the metropolitan area of Rio de Janeiro in the following decades. The end of the period coincides with the official formalization of the expression “Costa do Sol”, directly linked to the landscapes and bathing practices, to jointly designate the municipalities of the region.